Managing patients with multimorbidity in primary care - Al Yamani, Abrar Abdulfattah; Zamil, Bayan Talal; Alassaf, Mansour Assaf; Alamri, Assaf Hassan; Alshahrani, Mohammed Ayed; Alanazi, Mohammed Ghalab; Al Barak, Zahra Mustafa; Alamri, Faris Theyab; Alowaini, Abdullah Saleh; AlHawsawi, Sahar Yousef; Hilabi, Maha Ali (International Journal Of Community Medicine And Public Health, 2022)
Multimorbidity is usually described as the co-occurrence of two or more chronic medical conditions in the same individual and is related with a reduced quality of life, functional decline, and raised medical expenditure, along with emergency room visits, and specifically with elevated frequency of coexisting illnesses. Multimorbidity poses many difficulties, that can frequently be overburdening. With rising prevalence of multimorbidity across all age groups, both patients encounter many challenges including a sense of isolation in managing multimorbidity. Multimorbidity leads to fragmented care delivery and poorer perception of overall care coordination among patients. Polypharmacy and risks of adverse drug events; treatment burden on the patient, functional problems, especially in the elderly; reduced quality of life, and increased healthcare utilization. Adoption of a multidisciplinary approach in case management and a prioritization of generic outcomes applicable across comorbidities is recommended to achieve this goal. Management of medicines prescribed for multimorbidity is a significant aspect of improving care in patients with multimorbidity. Optimizing medication regimens is a crucial part of treatment and to acquire this, periodic medication reviews are necessary. Close cooperation among pharmacists and clinicians appears to be the most rational technique for this patient category. Medication reviewal must include “deprescription,” which implies cessation of medications which are not required, offer insufficient prognostic advantage, or are resulting in side effects. Comprehensive prescription guidelines may also be beneficial in maximizing the effectiveness of medications. The review also sheds light on the current research on strategies to improve organization and continuity of care, measures to promote patient-centered care, and the role of self-management education programs in multimorbidity.